Synthesis of Derivatives of Lanthanocene Complexes for the Isomerization of 1,5-Hexadiene - YOUSAF, MUHAMMAD; FAWAD ZAHOOR, AMEER; G. ALI, KULSOOM; BADARUDDIN AHMAD, HAFIZ; QIAN, YANLONG (Asian Journal of Chemistry, 2010)
The title complexes were prepared by the reaction of tris(cyclopentadienyl) lanthanides [Ln = Sm, Dy or Er] and tris(cyclopentadienyl)- yttirium with tridentate Schiff base, N-(2-methoxyphenyl)salicylidineamine in THF under argon at ambient temperature and were characterized by elemental analysis and spectroscopic techniques (MS and IR). These lanthanides complexes were applied for the isomerization of 1,5- hexadiene. The isomerization resulted into a mixture of 1,4-hexadiene and methylenecyclopentane as intermediate and 2,4-hexadiene and methylcyclopentene as end products. The ratio of the linear to the cyclic product in the reaction is dependent upon amount of catalyst used.